A modified protocol for high-quality DNA extraction from seeds rich in secondary compounds. Issue 5 (3rd September 2017) - Sudan, Jebi; Raina, Meenakshi; Singh, Ravinder; Mustafiz, Ananda; Kumari, Sumita
ABSTRACT: High-quality DNA is a prerequisite for a range of molecular biology experiments and thus DNA extraction is one of the most important steps for several downstream experiments. DNA isolation directly from seeds could save time and effort, particularly for large-scale experiments where growing and maintaining multitude of genotypes in parallel is cumbersome. However, seeds often contain polysaccharides, polyphenols, mucilage, oils, etc., which cause DNA extraction from seeds difficult and sometimes a research limiting step. In the present study, we have considered many previous protocols and optimized these methods to devise a general method for extraction of DNA from the seeds of diverse plant genera. The new SGS buffer (sucrose, glycerol and sodium dodecyl sulphate) was used to extract intact DNA from seeds with yield and quality better than in the previous protocols. Moreover, the proposed protocol is devoid of hazardous and expensive reagents and can be scaled up.